Optimal Exercise Boundary of American Put Option - LESTARI (NIM 20105001), RIRI
This work deals with American Put Option. Determining American Put Option is more difficult than European Put Option because the boundary is ambiguously known when the option must be exercised. This problem will be transformed to Partial Differensial Equation (PDE). The solution is obtained by using Green Function to convert the PDE to be integral equation. This integral equation is solved asymptotically. The result is optimal exercise boundary and the price of American Put Option.